THE IMPLEMENTATION OF ENGLISH LANGUAGE AS THE MEDIUM IN TEACHING SCIENCE TO THE EIGHT GRADERS OF “KELAS UNGGULAN” AT MTSN KEDIRI II (RETAIN, 2014)
THE IMPLEMENTATION OF ENGLISH LANGUAGE AS THE MEDIUM IN TEACHING SCIENCE TO THE EIGHT GRADERS OF “KELAS UNGGULAN” AT MTSN KEDIRI II Ana Khoirun Nikmah English Education Department, Language and Arts Faculty, Surabaya State University. Email: nikmeh08@gmail.com Rahayu Kuswardani, S.Pd, M.Appl English Education Department, Language and Arts Faculty, Surabaya State University. Abstrak Sesuai dengan program kelas unggulan, kelas yang semula hanya menerapkan proses kegiatan belajar mengajar dengan menggunakan Bahasa Indonesia sekarang diharapkan bisa menggunakan Bahasa Inggris dalam kegiatan belajar mereka, baik itu dalam hal mengajar maupun dalam pengajaran sesui materi pelajaran. Ini merupakan tantangan bagi seorang guru dalam menghadapi system pembelajaran seperti itu. Kompetensi dan keahlian guru yang baik sangat dibutuhkan dan juga dalam keseluruhan standar pengurangan Bahasa Inggris. Selain itu, system pembelajarn ini juga tidak semudah yang kita pikir. Mereka diharuskan belajar ilmu pengetahuan menggunakan Bahasa Inggris sebagai media proses belajar mengajar padahal mereka juga masih belajar Bahasa Inggris. Oleh karena itu, dalam penelitian ini, penelti melakukan penelitian yang bertujuan untuk memahami masalah diantara keahlian guru Bahasa Inggris dalam menguasai Bahasa Inggris ketika mengajar ilmu pengetahuan dan masalah siswa dalam memahami ilmu pengetahuan yang menggunakan Bahasa Inggris. Dari latar belakang yang sudah disebutkan tersebut, peneliti tertarik untuk melakukan penelitian berdasarkan situasi yand terjadi dengan judul “The Implementation of English Language as the Medium in Teaching Science to the Eight Graders of “Kelas Unggulan” at MTsN Kediri II”. Obyek penelitian dala penelitian ini adalah kompetensi gur ilmu pengetahuan dalam mengajar ilmu pengetahuan dengan menggunakan media Bahasa Inggris dan penerapannya dalam kegiatan belajar mengajar, masalah yang dihadapi guru ilmu pengetahuan selama kegiatan belajar mengajar di kelas delapan pada kelas unggulan MTsN Kediri II. Penelitian ini menggunakan penelitian deskripif kualitatif. Sedangkan subjek penelitian ini adalah kelas delapan pada kelas unggulan MTsN Kediri II. Dalam pengumpulan data, peneliti menggunakan dua instrument, yaitu catatan observasi dan wawancara. Catatan observasi dilakukan untuk mengetahui kompetensi guru dalam mengembangkan kemampuan Bahasa Inggrisnya dalam proses belajar mengajar. Sedangkan wawancara dilakukan untuk mengetahui usaha-usaha guru yang telah dilakukan mengembangkan dan mengatasi masalah dalam penggunaan Bahasa Inggris sebagai media pembelajaran. Berdasarkan observasi yang telah dilakukan, peneliti menyimpulkan bahwa kompetensi guru dalam berbahasa inggris harus dikembangkan, terutama kosakata dan strukturnya. Sedangkan dari hasil wawancara, peneliti mengetahui bahwa guru ilmu pengetahuan kelas delapan pada kelas unggulan MTsN Kediri II selalu mengembangkan kompetensinya untuk mengatasi masalah dalam kegiatan belajar mengajar dengan cara mengikuti kursus Bahasa Inggris dan bekerjasama dengan sebuah tempat kursus Bahasa Inggris di Kampung Inggris, Pare. Karena masalah utama di dalam kelas adalah penggunaan Bahasa Inggris pada guru dan pemahaman para murid, maka materi ilmu pengetahuan diberikan dengan tetap menggunakan Bahasa Inggris sebagai medianya. Keyword: kemampuan guru ilmu pengetahuan dalam berbahasa inggris pada “kelas unggulan” Abstract The term of “kelas unggulan”, which has been using teaching and learning in bahasa Indonesia is expected to perform effectively in English, to teach and acquire subject specific knowledge. It is one of challenges of teacher to face this reality. Good teacher’s competency and proficiency are needed and also overall declining standard of English. In the other hand it is not as simple as everyone think. They have to learn science using English as the medium of teaching and learning process whereas they also still learning English. Therefore, to understand the problem between the English teacher’s proficiency in mastery English language to teach science and the problem with the students understanding science in English. From the background above the researcher is interested in conducting research related to the situation, entitled “The Implementation of English Language as the Medium in Teaching Science to the Eight Graders of “Kelas Unggulan” at MTsN Kediri II”.The objective researches of this study are the science teacher competency in explaining science using English as the medium and the implementation of it, the problem faced by science teacher during teaching and learning process at Eight Graders in “kelas unggulan” at MTsN Kediri II. This research use descriptive qualitative research while the subject is Eight Graders in “kelas unggulan” at MTsN Kediri II. In collecting data the researcher use two instruments, they are observation field note and interview. The observation field note is used to know the teacher competency in improving her English while teaching and learning process. And the interview is used to know the effort of the teacher in improving and also facing the problem in using English as the medium of instruction. Based on the observation, the researcher concludes that the teacher’s competency in English needs to be improved, especially in vocabularies and structure. Then, from the interview the researcher knows that the science teacher of Eight Graders in “kelas unggulan” at MTsN Kediri II always improve her competency just to overcome the problem in teaching and learning process by taking English course and doing cooperation with one of big English course in kampong English, Pare. Because the main problems in the class are the English teacher and the students understanding the science material given using English as the medium. Keyword: Science Teacher’s competency in English in “kelas unggulan” INTRODUCTION In the current era of globalization, English language plays an important role in international communication. All of the aspects on live, like technology, economic, politic, art, education etc. use English Language to communicate. For example, in technology, we all know that Yamaha product is made in Japan. But when we read the direction note of Yamaha product, we will find some technical term used is English Language. We also can find this case in economic aspect. In a free market, if there are two seller were not come from English doing transaction, they will decide to use English Language to talk each other. So that is not surprising that English Language is known as the international language. In fact some countries in this world use English language to be their national language, like Singapore. And the other countries use English language as their second language besides their own national language. But in our country, Indonesia is still included in a country that used English as the foreign language. So that way is aware of along with the globalization, the need for an English language skill is increasingly apparent. Therefore, it is not surprising that experts who are involved in education feel the need to provide intensive English lessons and continuing English education to the students in middle school even since the children were still sitting in elementary school. Secondary school level has a lot of junior and senior high school who offer to ​​pioneer international standard school and has a lot of schools that obtain international school status. The schools, which obtain international status, prepare their students for the future so that they can compete globally. Recognizing the importance of quality in education and a desire to catch up education set back with other countries, governments are encouraged to perform a major breakthrough in the field of education by designing international school. The government wants to promote educational programs in the country by turning national schools into international standard schools. Schools must make an effort to improve the quality of teaching and teachers’ so that teachers’ quality will not be left behind. One of the schools that used international standard is MTsN Kediri II. MTsN Kediri II is a junior high school located in Kediri, East Java. It is included one of the favorite school in Kediri because almost of their students are smart enough and often be the winner in Olympiad. Since some years ago besides use national curriculum, this school also use international standard in their education. Because of that, they divided their class into some kinds of class. That is regular and kelas unggulan. Regular class is a class that use national curriculum in their teaching learning process. In other hand, the kelas unggulan is a class based on international standard. In kelas unggulan, some subjects such as Mathematics, Physics, Chemistry, Biology and Economics should be conducted in English or in a bilingual classroom learning environment. Bilingual education involves teaching academic content in two languages that is, in a native and secondary language with varying amounts of each language used in accordance with the program model. It is an educational approach that not only allows students to master academic content material, but also become proficient in two languages. It is an increasingly valuable skill in the early twenty-first century. It is the program which is intended to help children to keep up with their peers in subject such as math, science and social studies while they study English (Maria. 2001). The purpose of bilingual instruction is to increase academic achievement by using the student’s home language as the main communication medium. Bilingual instruction involves the use of two languages for instructions for part or all of the activities within the classroom. One language is English and the other language is the student’s home language that is the language spoken in the home. English is taught as a second language (James. 1988). Whether teaching a transitional class, a maintenance class, or a two ways bilingual class, the main difference from a monolingual class is the balance in using of the two languages. A second variable which affects the process of classroom organization is who teaches: a team, a teacher and an aide or one teacher alone. The third variable comes from the structure of the program model. There are the three major variations in classroom design which effect use of the two languages in a bilingual classroom. The first is The concurrent approach. In this approach A teacher using concurrent approach may use both languages interchangeable in a teaching content are or two teachers may team teach one lesson, each modeling a different language. The second is Pre-view-pre-view. It involves three steps in a team teaching situation: an introduction to the lesson is first given by one instructor in one language. The lesson is then presented in the other language by the second instructor. Review and reinforcement of the lesson takes place with the whole class using the two languages interchangeably in a concurrent approach, or the class is divided into dominant- language groups, led by each teacher separately. The last approach is Alternate language approach. Clearly structures a separation between the two languages. But for student is so limited proficiency in one of the language instruction, the language chosen for content area instruction can involve complex decision. In early stages, student should receive science lesson in their first language, but as they develop increasing proficiency in a second language, they may introduced to an increasing amount of science instruction in their second language. In the school that uses bilingual classroom system, the teacher must have two levels of language skills sufficient to be able to teach bilingual classes. But here, Sheelagh and Cristine (2007:6) divided two different types of teachers who have very different needs-the expertise of the language may not be shared by the content and vice versa. The first is Teacher of English who now has to teach another subject through English, rather than just teaching the language. And the other is subject teacher who now have to teach their subject through English. In this research, the researcher study about the second type of CLIL, that is subject teacher who now have to teach their subject through English, exactly science teacher. As Henderson and Wellington (2001:23) said that whilst research shows that one of major difficulties in learning science is learning the language of science, to experience the teaching and learning process would suggest that science teachers often consider the use of English in Biology lesson to be of marginal relevance to the learning of science (Henderson & Wellington. 2001:23) . They further add that in general, teachers who teach content do not recognize languages learning opportunities. If there is any effort at all in incorporating language development, they just concentrate on vocabulary development. John (1997:17) also said that some science teachers hope that the vocabulary of science will be recognized by the students as a key to its comprehension and appreciation. The teacher also must make avert efforts to interpret the nature of Biology lesson and the habits of learning Biology through its language or vocabulary. So we can conclude that science teacher must be competence in the both od the biology subject and English Language. The problem that we find in the reality is one cannot confirm that the subject teachers are able to become a bilingual who is ready to teach in two languages, Indonesian and English. How long does it take for a teacher to be ready to teach bilingual? In addition, the level of bilingual skills to a certain level is needed or that must be achieved by a teacher to be able to teach bilingual classes. Those subject teachers mostly of are not graduates of English Education, so maybe they will find difficulty in explaining their material in English. Therefore, the researcher wanted to conduct a research which intends to describe this phenomenon, the implementation of English language as the medium in teaching scdience at eight grade in “kelas Unggulan” at MTsN Kediri II. By conducting this study, the researcher has purpose to find out the implementation of English language in teaching science for eight graders and the teacher’s problems faced during classroom teaching and learning. By knowing the fact or the result of the study, the researcher hoped it will give meaningful contribution for The teacher who uses English, especially science teacher in “kelas unggulan” at MTsN Kediri II, can improve their ability in English and the quality of teaching and learning process, and also the result is expected to contribute development of teaching science by using English in “kelas unggulan” at MTsN Kediri. It is also expected to give meaningful contribution for Indonesian government. It is hoped that the government can consider about the programs to make Indonesia to become international level in education by using English in the process of teaching and learning process. According to the government it can make the education in Indonesia becomes better than before to the international level, people argue that it does not make better education in Indonesia, but it can make the education. Worse, since the students face more problems in their study due to their English ability is still poor. This phenomenon makes the researcher puts her interest to conduct research about it. The researcher questions: (1) how is the implementation of English language in teaching science for eight grader? (2) What problems do the teachers face during classroom teaching and learning? METHOD Based on the research question and the objective of the study, the researcher used descriptive qualitative. Gay (1992) explained that Descriptive research involves collecting data in order to answer questions concerning the current statues of the subject of the study). In this study, the researcher described the implementation of English language as the medium in teaching scdience at eight grade in “kelas Unggulan” at MTsN Kediri II. She concentrated on the biology class activity and the biology teacher herself. In this research, the researcher chose descriptive qualitative as the research design based on two reasons, which are the objective of this study is to describe the implementation of English language as the medium in teaching scdience at eight grade in “kelas Unggulan” at MTsN Kediri II and there is no treatment in this study. The subject of this study was the biology teacher of “kelas unggulan” in the 8th at MTsN Kediri II. The researcher chose the biology teacher because three reason. For the first, there are many students who favor Biology lesson. They like biology subject because biology is the easiest among Physic, Chemistry and Biology. The second reason is Biology lesson has a few things to be discussed about numerical, but it has many explanations. To give explanation a material in the Biology, teachers have to explain more. It means the teacher should make long sentences and more languages especially English. And the las reason is there is another language that is in Biology discussion, that is Latin language. Every plant or animals has Latin name, so students have to understand which Latin language is and which is English. This study is taken place in the 8th “kelas unggulan” and the teacher’s office. For the first day, the researcher observes the condition of the school and the Biology teacher’s when she was teaching in the classroom. The researcher recorded the teaching and learning process using vidio camera and tape recorder. And on the next day, the researcher came to the teacher office, actually on the biology teacher’s room to interview her. The interview was used to find the data form the Biology teacher. The purpose of this interview was also to find out the information about teacher’s efforts in developing the English language competency and to find out what the problems she usually faced during teaching and learning Biology by using English language. After knowing the problem, researcher could infer reasonable solution to solve the problems that were faced by the teacher. The data of this study is the condition of the biology class on 8th “kelas unggulan” in MTsN Kediri II. It included the teacher’s competence in giving oral instruction by using English language in her Biology science class, for example asking question in English, giving opinion, giving explanation in English and the students’ expression and utterance during teaching leraning activity. The other data is teachers’ answer in the form of utterances and expressions given by the teachers during interview sessions which are transcribed into written form. Besides the result of the researcher’s observation, the source of the data is the biology teacher herself. In this research, all of the data were collected by using observation field note and interview, were analyzed inductively in order to answer research questions stated in chapter one. The first step was accumulating the data recorded from the result of class observation and the answer of biology teachers through interview given. After all of data accumulated, the researcher studied the data well, she described them by classifying into the finding based on the research question. In addition, all the data were collected thoroughly as happened in the reality. RESULT AND DISCUSSION This chapter presents the result and discussion of the study as the answers for the research questions: (1) how is the implementation of English language in teaching science for eight grades? (2) What problems do the teachers face during classroom teaching and learning? Result Here, the researcher explained about the first and second day observation done by the researcher. On the first day observation, the researcher observed the condition on 8th kelas unggulan of MTsN Kediri II. In the first observation, the researcher noticed some facts happened in their teaching learning activities. Those are: (a) when the teacher explains the material by using English, her explanation is difficult to be understood by her students. (b) The science teacher of “kelas unggulan” in MTsN Kediri II does not always use English in explaining science material. (c) When the teacher wanted to explain about the material, she was consuming too much time to find the proper words makes the students waiting for long time, and also makes them getting bored. (d) the teacher often feels nervous and automatically, she cannot control her speaking, especially in pronunciation and vocabulary. In term of pronunciations, the researcher finds some words mispronounced words form, it was pronounced this word as like forem. In the word size, it is pronounced with sez. (e) The teacher thinks that the use of translation method make the students understands the material well. So that, in the most of the time she explains the material by using mother tongue then translate in to the English. (f) Because the teacher is fully aware that she is not teaching language at all but teaching science. So, she thinks that it’s not to importance to make her English perfect. It is better to teach real science rather than just focusing on the students’ English skills. (g) There are three languages used in the class there are (Indonesia, Javanese and English). But the biggest portion, about eighty percent used Indonesian. On the second day of this research, the researcher done interview the biology teacher of 8th “kelas unggulan” in MTsN Kediri II. From the interview which was done on May 23th 2013, the researcher tried to analyzes the teacher efforts in improving her skills in English language. There was one teacher who was interviewed by the researcher. Mrs Zahra’, she is science teacher in the eighth graders of MTsN Kediri II. Science Teacher stated that, actually, she has already tried her best effort in improving English skills. It was done by practicing the speaking skill with her daughter and son at home. Her children convinced their mother that if she always does not speak English continuously and regularly as her daily habit, it will really improve her English. Besides the effort or practice she does at home, she also joins the English course which is hosted by the school in cooperation with one of good English course in Pare. These are proves that both school wants to improve the English ability so that she teaches science by using English confidently. Besides that, the school also held TOEFL and TOEIC test to know whether the competency of the teacher has improved or not. The Teacher’s Competency in using English as the Medium of Teaching Science Teacher ability plays important role in delivering new knowledge and skills to students. If the teacher wants to be regarded as excellent and competent teachers by parents based of the excellent academic achievement of the student the teacher have to works hard to get it. In the implementation of the teaching Science in English in kelas unggulan, teacher’s competency in teaching the subject is really needed, it include in the way the teacher teaching, teaching strategy, etc. This is so because many of our teachers today have had very little exposure to the subjects in English. In this research, the researcher explained about science teachers’ competency which contains the ability to ask question in English, the ability to use oral instruction in English and the ability to give opinion in English. The Teacher’s Ability in Questioning Student In the teaching and learning process in teaching science by using English as the language medium, the science teacher of Kelas unggulan at MTsN Kediri II is expected to be able to ask question to their students about the material that she had explained by using English. If it runs well, of course, it will make the students motivated during question and answer session. However, the teacher which is expected to be a model that has perfect examples how to ask thing in English did not do so. So that way, their students also answer the question in mixed language. Based on the observation done by the researcher, the researcher conclude that the science teachers in Kelas unggulan of eight graders of MTsN Kediri II still use translation method, that she use both English and Indonesia in asking question. This condition happened because both of the teacher and student do not master English well. To her observation, both the kelas unggulan students and the teacher are have not ready to use English one hundred percent yet in the class. Even though the researcher had to agreed that the use of English one hundred percent is too difficult for students, simply because the science language is different from the English that the students are studying during English class, the teacher as the important point should push herself to use English as close as possible at least they have to reach 75% during the teaching and learning process especially in asking question. Of course, the English foreign learners or English second learners will get some difficulties to express science term in English, but they have to work hard if they really want to make the bilingual runs well. The Teacher’s Ability in Giving Oral Instruction by Using English In the process of teaching and learning science using English as the language medium, the science teachers of MTsN Kediri II always tried to give oral instruction to her students beside the written instruction. These two important are things which cannot be separated one by one. It is important to oral instruction during the teaching learning process, because without oral instruction the communication in the class between teacher and students cannot runs well. In this case, as a science teacher does oral instruction to help her students to understand the task easily. However, the simple interaction only done in Indonesian language, not in English because, the teacher still has difficulty to make simple interaction by using English. Based on the result of observation, the researcher concluded that the science teacher of MTsN Kediri II tried to maximize her ability in using oral instruction in English even though it is not grammatically correct. She tried and sometimes she mixed it with Indonesian. The problem is of mixing the language because, she still uses Indonesian quite a lot when giving her oral instruction. Based on the researcher observation, the science teacher of Kelas unggulan should master the art of giving oral instruction in English to communicate with their students if she wants to make the class become the real bilingual or international standard class. The Teacher’s Ability in Giving Opinion to the Students Teaching through another language for some subjects may have cause a language problem. It happens in this class also when the teacher expresses her opinion in English; she mixed it with Indonesian language. Seems that she still find difficulties. It can be frustrated for the teacher to teach subject that have different language vocabularies, especially science subject. The language for science is different from the English language which students use in English class activities. Vocabulary in Science class has special syntactic structures. Making inferences in science subject meaning give all contribute to the difficulties of many other subject subjects which use English so. The selected teacher who teaches science by using English as the language medium of interaction for Eight graders in MTsN Kediri 2 has tried to maximize her ability in using English. During classroom activities the science teacher sometimes mixed the language when she was giving her opinion to the students. The Teacher’s Efforts in Improving her English Teaching Skills From the observation and the interview that has been conducted, the researcher finds some mistakes of the science teacher in expressing sentences and words in spite of her mistakes. The mistakes include the teacher still tries her best effort to use English in explaining all the science materials. In the contrary to the teacher’s effort, most of the mispronouncing the words and mixing the languages between English and Indonesian, students are still difficult to handle the maximum usage of English. They have to understand the science material in English is a big challenge to them. Therefore, to maximize her students’ difficulty and to overcome the challenge, teacher uses Indonesian in some of explanations. Based on the result of observation, it can be concluded that sometimes the science teacher mixed the language or does not use English at all when she was not sure with the English Especially, if the teacher who does not have a good competency with her English language. The requirements to use English can be serious problem. From the interview that has been done the researcher find some facts that: First, the science teacher doesn’t have good ability in speaking English or explain the science term correctly in English. Based on that, she gets difficulties in delivering the content to the students. Second, seems that science teacher is not too familiar with the terminologies and science terms in the English language due to her minimal exposure for learning and teaching science in the English language. Since the school supports the Implementation English in science class. The teachers’ competency in teaching subject needs to be improved immediately. It is so because many of science teachers in that school have had very little experience in exposure English as the language medium in the classroom especially for the class that is chosen as kelas unggulan. The Problems Faced by the Teacher During Teaching and Learning Process There were some problems faced by science teacher of Kelas unggulan in MTsN Kediri II during teaching and learning Science by using English. The main problem of successful in using English in kelas unggulan is from the students’ ability to understand the material which is presented in English. This fact is also confirmed by the science teacher, Mrs. Zahra’ who is the teacher of science in “kelas unggulan” of MTsN Kediri II for class said that her problem during classroom explanation when she was teaching science refer to the language competency of their students in order to understand the science language in English. She stated if the students did not understand the language, it shows that they also would not be able to do the science task correctly. The solution of this problem according to her is giving some vocabularies continuously to the students who have the difficulties in understanding the science language. One more thing that in MTsN Kediri II there are some teams which is have quite good members who has cooperation with an English course in Pare. It was had been for about 3 months. So, it means the groups still in the process of improvement. The science teacher who has a team teaching in the process of teaching science for the class of Kelas unggulan have the different problem. She said that the problem which is occurred in the process of teaching science not only the language problem but also less motivation and participation of the students to follow the class activities. The solution according to her is using different kind of teaching strategies and giving motivation to their students in every meeting. From the statement above, it can be known that every science teachers who teach using English have their own problems, and they also have their own solution to improve the skill of their students in science, besides the using various kind of learning strategies which will make the teaching learning process enjoy full. CONCLUSION AND SUGGESTION Conclusion Based on the finding of data analysis and discussion in previous chapter, the researcher drew a conclusion: First, from the result of the research analysis, it is proved that the students’ understanding of science’s class taught by using English as the medium of teaching and learning science process still have no improvements, and based on the result of research question by using interview, shows that using of English as medium of teaching and learning process is not quite effective for of MTsN Kediri II. It’s not because of just the teacher’s ability, but also the students’ English especially in understanding the words or vocabulary influence the result of learning, and in this school there are still some reasons that make the school has not been ready in applying English in teaching science, seen from the teacher’s English ability and also the lack of the students’ vocabulary on the lesson. Second, the use of English as the medium of teaching and learning science process in the science class makes the students are unable to enjoy their learning activities as well as the technique of the teacher use is not quite attracting them, and they can not understand the English teacher’s explaination well. It seems that the teacher’s technique cannot help them reduce the students’ anxiety of learning. In addition, it cannot make them feel comfortable in learning to lead them to be better in learning. Meanwhile the goal of applying English in teaching science is that the students have to be brave to say or to express their idea in English, and the teacher’s motivation is to make them confident to share the ideas. Third, the use of English as the medium of teaching and learning science process to the eight graders of MTsN Kediri II cannot seem to change the atmosphere of the classroom and is also unable to broaden their knowledges. Actually, it offers much wider range of language opportunities but what has happened there, the students have more difficulties in expressing the ideas, the correct vocabulary and sentences. Fourth, the use of English as the medium of teaching and learning science has made the class less active. The students do not have great willingness to participate without being forced by the teacher and they are still afraid of making mistakes in expressing the ideas. Fifth, the use of English as the medium of teaching and learning science makes the students less motivated in learning and are easier to grasp the lesson. Based on the observation has been done by the researcher there are just few students who have a bravery to express their ideas. Sixth, the other problems the students face are mostly in expressing ideas in English and lack of confidence and vocabulary. Suggestions The success in teaching not only depends on the lesson program, but also what is more important is how the teacher presents the lesson and uses various techniques to manage the class more lively and enjoyable. Regarding to the teaching science by using English as the medium of teaching and learning process, the writer gives some suggestion for the teacher. The science teacher should choose the materials that are appropriate and not too difficult for the students, the teacher should make sure that the students have fully understanding and enough information they need before assigning English as the medium of teaching science to the students, the teacher should keep controlling the student activities, the teacher should present the language in an enjoyable, relaxed and understandable way in order to make the students are attracted and enjoyed the science materials in English. Besides, the researcher suggests to the students. The students are hoped not to be shy in expressing the idea in English, to be active and creative in enriching their vocabulary, to use English when they practice or express the ideas although it is hard for them, the students should take part in teaching and learning process since being active in the class is needed. REFERENCES Collier, Virginia P. A Synthesis of Studies Examining Long-Term Language Dellar, Sheelagh and Christine Pierce. 2007. Teaching Other Subject Through English. New York: Oxford University Press. Page 6-7 Estela, Brisk, Maria. 2001. Bilingual Education from Compensatory to Quality Schooling. New Jersey London : Baston University Gay, L.R. 1992. Education Research Competencies for Analysis and Application Fourth Edition. New York: Florida International Universities Honbry,A S. 1995. Oxford Advanced Learner’s Dictionary of Current English Fifth Edition. Walton Street: Oxford University Press. Page 595 James, H. 1992. Education Research. New York : Hopper Collins Publisher Jarret, Dense. 1999. Teaching Mathematics and Science to English Language –Learners. Alaska : Nortwest Regional Education Laboratory Jinsook Choi and Joel Kuipers . Bilingual Practices in a Science Classroom Minority Student Data on Academic Achievement Washington, DC: National Clearing house for Bilingual Education. Page 87 Ovando, Carlos J.and Virginia P Collier. 1985. Bilingual and Esl Clasroom. New York : Mc Graw-Hill. Page 38 Robert C. Bogdan and friend. 1992. Qualitative Research for Education second edition. London: Ally and Bacon. Page 30